Chapter 10: Public encounters and the role of citizens' impression management - Oldenhof, Lieke (Edward Elgar Publishing, 2022)
Public encounters can be viewed as the communicative 'in-between' in which citizens and street-level bureaucrats define the situation in an orientation towards each other (Bartels 2013). Even although at first glance the interaction may seem highly unequal in terms of status and the ability of street-level bureaucrats to determine access to public services, citizens can strategically influence the impression that they create and redefine the situation. In this chapter we empirically examine how citizens conduct impression management during public encounters based on ethnographic observations and interviews in the Dutch social care domain. Theoretically, we draw on the work of Goffman (1990) and others to show how citizens rehearse their performance before the public encounter and engage in impression management during the encounter by setting the stage, mobilizing life narratives and using material props. The analysis reveals frictions between attempts by street-level bureaucrats to promote self-reliance and attempts by citizens to create the impression of need that justifies access to public services in times of austerity. Based on our findings, we reflect on the subtle power dynamics in public encounters and specify how micro-sociological studies of everyday interactions can potentially enrich macro institutional analysis of changing welfare states.